Spawning areas and migration patterns in the early life history of Squalius cephalus (Linnaeus, 1758): Use of otolith microchemistry for conservation and sustainable management. Issue 10 (25th August 2021) - Bounket, Bernadette; Tabouret, Hélène; Gibert, Pierre; Bareille, Gilles; Pecheyran, Christophe; Carrel, Georges; Argillier, Christine; Morat, Fabien
Abstract: In the context of the River Rhône restoration programme, the objective of this study was to assess the dispersal and population connectivity of the European chub, Squalius cephalus (Linnaeus, 1758) in a section of the natural, free‐flowing part of the lower River Rhône. The elemental water signatures for Sr:Ca and Ba:Ca were measured at seven stations within the river section, including its tributaries and backwaters, to determine whether they could be differentiated by microchemistry. From August to October the signatures differed among three sectors of the study reach: the Rhône; the Ardèche; and the backwaters. The elemental signatures of the otoliths of 178 young‐of‐the‐year (YOY) chub from the stations were measured to assess spawning areas and identify early migratory life histories. Analyses of otolith microchemistry identified the natal origin of 95% of the fish. Sr:Ca signatures of otoliths showed early downstream migration for 30.4% of the YOY chub; however, 70% of the fish recruited relatively close to their spawning origin suggesting a potential inshore retention of fish. The results showed (i) a non‐negligible contribution of the tributaries and backwaters in the recruitment of fish into the main channel; and (ii) the ability of chub to migrate over several kilometres during their first few months of life. This study shows that the combination of water and otolith microchemistry analyses of fish growth increases the understanding of fish life history. Moreover, the study revealed that half of the YOY fish from this river section came from the tributaries and the other half came from reproduction in the River Rhône (despite its high anthropization). These methods offer promising future applications of otolith microchemistry for river management in the context of ecological rehabilitation, especially to assess the effectiveness of measures applied in the restoration of floodplain connectivity for riverine fish population conservation.